2019
DOI: 10.7150/jca.34650
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate Overcomes Oxaliplatin Chemoresistance in Colorectal Cancer through the miR-543/PTEN/Akt/mTOR Pathway

Abstract: Chemoresistance is responsible for most colorectal cancer (CRC) related deaths. In this study, we found that dichloroacetate (DCA), a pyruvate dehydrogenase kinase (PDK) inhibitor, can be used as a sensitizer for oxaliplatin (L-OHP) chemoresistant CRC cells. The aim of this study was to explore the ability of DCA to overcome L-OHP resistance in CRC cells and to identify the underlying molecular mechanisms. We found that DCA sensitizes chemoresistant CRC cells to L-OHP-induced cytotoxic effects by inhibiting cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 31 publications
2
70
1
Order By: Relevance
“…In fact, apoptosis is the main mechanism for tumor cell death in response to antitumor drugs and, therefore, a molecule that induces drug resistance is expected to have antiapoptotic effects. Antiapoptotic effects have been demonstrated for glycolytic metabolism in general [49 , 98 , 112] and for individual components of it: enzymes like HK2 [16] , PFKFB3 [49] , PFK platelet type P (PFKP) [121] , ENO1 [56 , 95] , PKM2 [18 , 59 , 94 , 109 , 122] , LDHA [123] , PDK isoform 1 (PDK1) [73 , 124] , metabolites like pyruvate [78] , lactate and lactate-induced acidosis [87] . Antiapoptotic effects are achieved in several ways.…”
Section: Mechanisms Underlying Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…In fact, apoptosis is the main mechanism for tumor cell death in response to antitumor drugs and, therefore, a molecule that induces drug resistance is expected to have antiapoptotic effects. Antiapoptotic effects have been demonstrated for glycolytic metabolism in general [49 , 98 , 112] and for individual components of it: enzymes like HK2 [16] , PFKFB3 [49] , PFK platelet type P (PFKP) [121] , ENO1 [56 , 95] , PKM2 [18 , 59 , 94 , 109 , 122] , LDHA [123] , PDK isoform 1 (PDK1) [73 , 124] , metabolites like pyruvate [78] , lactate and lactate-induced acidosis [87] . Antiapoptotic effects are achieved in several ways.…”
Section: Mechanisms Underlying Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…For example, metformin for diabetes is effective for pancreatic cancer, lung cancer, and ovarian cancer 35 37 ; aspirin for cardiovascular diseases is effective for hepatocellular carcinoma, prostate cancer, and gastric cancer etc 38 40 . Notably, we recently found that dichloroacetate (DCA), which was originally used to treat lactic acidosis, hereditary mitochondrial metabolism disorder and diabetes, may restore chemosensitivity in CRC cells 41 43 . Therefore, it is valuable to explore the pharmacological effects of existing drugs for saving medical resources, improving the life span and quality of life of patients by repurposing traditional drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting point is that anti-tumor compounds including cryptotanshinone suppress cancer proliferation and induce apoptosis via PTEN upregulation and the subsequent inhibition of PI3K/Akt/mTOR and nuclear factor-kappaB (NF-ĸB) pathways [ 89 ]. Dichloroacetate can suppress chemoresistance in cancer cells via the downregulation of miRNA-543, upregulation of PTEN, and inhibition of the PI3K/Akt axis [ 90 ]. EMT is associated with the metastasis of cancer cells [ 81 , 91 ].…”
Section: Pten In Oncologymentioning
confidence: 99%